SIR: exploring the significant role of phonetics in the teaching of pronunciation / Sueb Ibrahim ... [et al.] - Ibrahim, Sueb; Noyan, John Francis; Metom, Lilly; Ismail, Ismariani; Bohari, Zubaidah (UiTM Press, 2020)
Pronunciation is one of the most overlooked aspects of English language teaching, despite the fact that its accuracy is the basis for effective communication in English. Malaysian learners generally encounter challenges in pronouncing English words due to the fact that there are many English phonemes (i.e. 44 phonemes). Hence, this study has developed an essential and practical tool called SIR to help learners pronounce the English words correctly with the aid of phonetic sounds and symbols. SIR stands for ‘Say It Right’, which is an interactive multimedia software that emphasizes phonetic sounds and symbols from the English phonemes. SIR’s novelty lies in its specific focus on commonly mispronounced words in English and the phonological awareness the software introduces into the learner’s cognition to facilitate comprehension and production Taking phonetics as a framework, SIR makes use of the different components of English phonetics in order to apply them in the software. The tool guides learners on the correct pronunciation of English words based on the 44 English phonemes. Since English spelling is not a reliable guide to pronunciation, the phonetic symbols serve as a dependable guide to correct pronunciation.